Electricity Economics and Integrated Resource Strategic Planning (Gustav Ranis Lecture) (The Pakistan Development Review, 2013)
Electricity supply economics and electricity demand economics are the two major components of electricity economics. This paper discusses the production functions with electricity, a core principle of electricity demand economics. In this paper, production functions with electricity are introduced at the firm level, sectoral level, industrial level, and national level. This paper also discusses integrated resource strategic planning (IRSP). As a part of electricity supply economics, it is a useful tool for policy study on low-carbon electricity. During the national economic development, low-carbon electricity can be recognised as the IRSP and the implementation of smart grid. The low-carbon electricity would be a great roadmap to Pakistan’s economic development. Pakistan’s economy is in an early phase of industrialisation. China’s economy is in the late phase of industrialisation. Experiences and lessons from China’s economic development would provide references to Pakistan. Keywords: Electricity Economics, Production Functions with Electricity, Integrated Resource Strategic Planning (IRSP), Low-carbon Electricity, Pakistan, China